Nanoscale Effects of Caspofungin against Two Yeast Species, Saccharomyces cerevisiae and Candida albicans - Formosa, C. (American Society for Microbiology, 2013)
Saccharomyces cerevisiae and Candida albicans are model yeasts for biotechnology and human health, respectively. We used atomic force microscopy (AFM) to explore the effects of caspofungin, an antifungal drug used in hospitals, on these two species. Our nanoscale investigation revealed similar, but also different, behaviors of the two yeasts in response to treatment with the drug. While administration of caspofungin induced deep cell wall remodeling in both yeast species, as evidenced by a dramatic increase in chitin and decrease in β-glucan content, changes in cell wall composition were more pronounced with C. albicans cells. Notably, the increase of chitin was proportional to the increase in the caspofungin dose. In addition, the Young modulus of the cell was three times lower for C. albicans cells than for S. cerevisiae cells and increased proportionally with the increase of chitin, suggesting differences in the molecular organization of the cell wall between the two yeast species. Also, at a low dose of caspofungin (i.e., 0.5× MIC), the cell surface of C. albicans exhibited a morphology that was reminiscent of cells expressing adhesion proteins. Interestingly, this morphology was lost at high doses of the drug (i.e., 4× MIC). However, the treatment of S. cerevisiae cells with high doses of caspofungin resulted in impairment of cytokinesis. Altogether, the use of AFM for investigating the effects of antifungal drugs is relevant in nanomedicine, as it should help in understanding their mechanisms of action on fungal cells, as well as unraveling unexpected effects on cell division and fungal adhesion.